Genetic association between intronic variants in AS3MT and arsenic methylation efficiency is focused on a large linkage disequilibrium cluster in chromosome 10 - Gomez-Rubio, Paulina; Meza-Montenegro, Maria M.; Cantu-Soto, Ernesto; Klimecki, Walter T. (Journal of applied toxicology, 2010)
Differences in arsenic metabolism are known to play a role in individual variability in arsenic‐induced disease susceptibility. Genetic variants in genes relevant to arsenic metabolism are considered to be partially responsible for the variation in arsenic metabolism. Specifically, variants in arsenic (3+ oxidation state) methyltransferase (AS3MT), the key gene in the metabolism of arsenic, have been associated with increased arsenic methylation efficiency. Of particular interest is the fact that different studies have reported that several of the AS3MT single nucleotide polymorphisms (SNPs) are in strong linkage‐disequilibrium (LD), which also extends to a nearby gene, CYP17A1. In an effort to characterize the extent of the region in LD, we genotyped 46 SNPs in a 347000 base region of chromosome 10 that included AS3MT in arsenic‐exposed subjects from Mexico. Pairwise LD analysis showed strong LD for these polymorphisms, represented by a mean r2 of 0.82, spanning a region that includes five genes. Genetic association analysis with arsenic metabolism confirmed the previously observed association between AS3MT variants, including this large cluster of linked polymorphisms, and arsenic methylation efficiency. The existence of a large genomic region sharing strong LD with polymorphisms associated with arsenic metabolism presents a predicament because the observed phenotype cannot be unequivocally assigned to a single SNP or even a single gene. The results reported here should be carefully considered for future genomic association studies involving AS3MT and arsenic metabolism. Copyright © 2009 John Wiley & Sons, Ltd. Several AS3MT single nucleotide polymorphisms (SNPs) that previously were associated with arsenic methylation efficiency have also shown strong linkage‐disequilibrium (LD) in the genomic region including AS3MT. To characterize the extent of LD in this region, 46 SNPs were genotyped in chromosome 10. Strong LD was observed spanning a region that includes AS3MT and four other genes. Genetic association analysis confirmed the association between this large cluster of linked polymorphisms and arsenic methylation efficiency.